BENTENG LITERASI DIGITAL: MENGASAH KEMAMPUAN SISWA DALAM MENCEGAH PENYEBARAN INFORMASI NEGATIF DI MEDIA SOSIAL DI MTSN 04 FLORES TIMUR - Krisroforus Pai; Donna Isra Silaban (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The spread of negative information on social media is of particular concern in today's digital era. The younger generation needs to be equipped with the knowledge and skills to prevent the spread of negative information on social media. This community service was carried out for MTsN 04 East Flores students. In this activity, servants carry out participatory socialization regarding digital literacy, teach information verification techniques, develop critical skills, and build digital ethics to prevent the spread of negative information or content in the digital environment. The results obtained show that students do not yet have this ability. However, this socialization helps them have the ability and awareness about digital literacy when surfing the internet.